Comparison of the match running demands of elite and sub-elite women`s Australian Football - Clarke, A. C.; Couvalias, G.; Kempton, T.; Dascombe, B. (Science and Medicine in Football, 2019)
Objectives: This study aimed to quantify and compare the match running movements of elite (AFLW) and sub-elite (VFLW) women`s Australian Football (AF) competitions. Methods: Match running movements (GPS) were recorded during 7 AFLW (n = 91 files) and 13 VFLW (n = 263 files) competition matches. Results: AFLW players covered moderately greater relative high-speed running (HSR, 14.4-18.0 km/h, AFLW 14.9 ± 5.7 m/min; VFLW 12.2 ± 3.9 m/min; ES = 0.61, ±0.39), very high-speed running (VHSR, 18.0-20.0 km/h, 4.2 ± 2.0 m/min; 3.2 ± 1.4 m/min; ES = 0.61, ±0.14), and sprint (>20 km/h, 3.3 ± 2.2 m/min; 2.1 ± 1.6 m/min; ES = 0.65, ±0.16) distances than VFLW players. Small to large differences were apparent within positions between competitions for HSR, VHSR, and sprint distances, most notably in small forwards (ES = 0.78-1.45). VHSR and sprint distances decreased in the fourth quarter when compared with quarters one and two (ES = 0.22-0.33) in the AFLW competition, whereas VFLW match running movements remained consistent across quarters. Conclusions: These differences may reflect the variations in match rules between competitions (fewer on-field players and shorter match time in AFLW), providing greater on-field space per player and interchange frequency. This information can assist in prescribing appropriate training for women`s AF competition.